Role of Cu foil in-situ annealing in controlling the size and thickness of CVD graphene domains. (April 2018) - Huet, Benjamin; Raskin, Jean-Pierre
Abstract: Producing graphene with minimal crystalline defects and a controllable number of layers is highly desirable for its integration in advanced technological applications. Here we show how the chemical vapor deposition (CVD) protocol can be adjusted in order to control the size, the shape and the thickness of graphene domains. More particularly, this work focuses on the correlation between the conditions employed during the Cu foil in-situ thermal treatment and the subsequent graphene growth. The influence of Cu pre-growth treatments has been systematically investigated by considering two different pressure regimes (1 and 800 mbar) and various gas compositions (pure Ar, Ar/H2 and Ar/O2 mixtures) while using identical graphene growth conditions. We show that exposing the Cu foil to oxygen, either present as residuals in the Ar feedstock or precisely dosed using the Ar/O2 gas line, effectively contributes to reduce the catalyst carbon content prior to graphene growth and hence significantly decreases the nucleation site density. It is also found that annealing the Cu catalyst in a hydrogen-free environment favors the formation of defect-free multi-layer graphene branches that extend underneath the millimeter-size single-crystalline graphene top layer. Our results provide clear guidelines to control the formation of graphene nuclei and additional layers. Graphical abstract: Image 1